Dampak Asimetris Pembangunan Flyover: Sektor Logistik dan UMKM di Kota Bandar Lampung - Muhammad Rifky; Erlin Kurniati (Yayasan Literasi Sains Indonesia, 2026)
The construction of flyover infrastructure in Bandar Lampung City is a spatial engineering initiative aimed at resolving traffic congestion caused by increasing vehicle volumes. This study analyzes the asymmetric impact of flyover operations on the efficiency of logistics distribution and the sustainability of Micro, Small, and Medium Enterprises (MSMEs). This qualitative research employs a structured content analysis method on secondary data, obtained from government agencies and previous literature. The results indicate that this infrastructure demonstrably reduces transit times for commercial vehicles and systematically lowers operational costs in the macro-scale logistics sector. Conversely, at the micro level, the physical construction triggers external diseconomies for MSMEs located beneath the structure due to the permanent loss of parking spaces and reduced visibility. This phenomenon presents an infrastructure paradox, where the impediment to physical interaction simultaneously facilitates easier access for digital logistics. In response, MSME actors are compelled to implement electronic marketing strategies to sustain their businesses. Local governments need to formulate inclusive spatial planning regulations for under-bridge areas to restore spatial equity.